Communicating about inter-ethnic unity: an investigation on differences between youths of the three main ethnic groups in Malaysia - Arina Anis Azlan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In a multicultural, multi-ethnic and multireligious country such as Malaysia, inter-ethnic unity is considered both enriching to society and a challenge for government. A diverse population with variations in culture, language and religion is often perceived as difficult to govern due to the many different needs, values and expectations of different groups within a multicultural society. Malaysia is often lauded for the inter-ethnic harmony and stability of its society that allows the country to flourish economically. Though there is no violent conflict between the ethnic groups, a sense of national unity proves challenging to achieve as ethnic divides exist along political, socio-economical and geographical lines. This study was conducted to investigate how Malaysian youth participate in the conversation about inter-ethnic unity. Utilising measures of Communicative Actions in Problem Solving from the Situational Theory of Problem Solving (STOPS), a survey was distributed among 575 university students from four institutions of higher learning in the Klang Valley, Malaysia. A one-way multivariate analysis of variance was conducted to determine whether there were any differences between the three main ethnic groups on the six different communicative behaviours pertaining to the issue of inter-ethnic unity. The results showed that there were significant differences in information seeking, information forwarding and information sharing. Among these behaviours, the differences between the Malays and the Chinese were most prominent whereby the Chinese showed relatively lower levels of information seeking and sharing compared to the Malays, and lower levels of information forwarding compared to both the Malays and the Indians.